Measuring System of Temperature, Humidity, and Light Intensity for Plant Monitoring in BALITJESTRO, Batu City - Tomy Andre Ansyah; Heriyanto Heriyanto; Buyung Al Fanshuri (Universitas Negeri Malang, 2021)
Therefore, a tool is needed to make it easier for researchers, so there is no need to go back and forth to retrieve data. This research has the following research method stages, (1) literature study of theories to design the system from the tools to be made, (2) system design, (3) analysis of device requirements, (4) tool calibration process (data can be said to be valid if the error does not exceed one per cent), and (5) data processing is according to agricultural research needs. In this research, a tool that has calibrated with an appropriate measuring instrument produced. Measuring temperature, humidity, and light intensity designed with a microcontroller and other sensors with a data storage base on an SD card. The measuring results show that the temperature values fluctuate between 16.9 °C to 28.2 °C. The value of air humidity tends to remain at the value of 99.9 per cent. At the same time, the value of light intensity ranges from 332 to 606 Cd. The relative error of temperature, humidity, and light intensity is 0.007, 0.082, and 0.016 per cent respectively. Therefore, each measurement indicator has a relative error value of less than one per cent so that the designed tool has valid and under the standardized measuring instrument.DOI: 10.17977/um024v6i12021p033